A study on a new design of semi-automatic crepe machine to improve Small Medium Enterpise (SME) productivity - Noraniah; Mohammad Noor, Hafsa; Bernadette, Leong Ming Xin; Hashim, Ahmad Ruzaini; Muhamad Fadzir, Muhammad Amirulhusni; Tuan Ibrahim, Tuan Mohd Hafeez (Multidisciplinary Applied Research and Innovation, 2020)
This paper presents a study on a new design of semi-automatic crepe machine to improve Small Medium Enterprise (SME) productivity. Currently, they are used the manual method to make crepes layer. This method is low efficient because the speed and output production completely depends on human effort and skill. Therefore, a semi-automatic machine has been designed to improve productivity that focusing on crepe layer making process. This machine parts and assembly model were designed in virtual by using SolidWorks 2019. The parts function and suggested material will be used also has been identified. Then, power transmission results have been obtained through analytical referring to specification data of this machine’s component such as DC motor, bevel gear and spreader. The result found, the output speed, torque and power have been transmitted from motor to spreader during spreading batter on a pan is 50.01RPM, 41.24 Nm, 216 Watt respectively with assumed 90% efficiency. Next, a simulation of transient thermal finite element analysis (FEA) was conducted on spreader with heating to 100℃ the contact surface in different temperature by using Solidwork 2019. The variable heating times of 1, 60, 120, 240, 360 and 480 minutes respectively have been used. The simulation result has determined that the maximum heating period for spreader is allowed contact on a hot pan as continuously is a limit to 120 minutes (2 hours). Afterwards, following the crepe cake process time analysis between of manual, expertise and this semi-automatic machine, the result was found the production speed by using Semi-automatic machine contributes 36.8% increase compared to the manual method by a beginner. While the crepe cakes output in 8 hours production run will provide a 66.7% increase when using the semi-automatic machine compare to the manual method by a beginner. Lastly, referring to the results of this study, this new design of semi-automatic crepe machine able to improve the Small Medium Enterprise (SME) productivity. The added value, this machine proven heat resistant and safe use for the user.